An introduction to mechanisms in pharmacology and therapeutics - Rogers, Howard John.; Spector, Roy (London, United Kingdom : William Heinemann Medical Books LTD, 1976)
This book is primarily intended for preclinical and clinical medical students and those preparing for an honours B.Sc degree in pharmacology.
1.The cell and drugs -- 2. Drug-receptor interactions -- 3. Cell membranes -- 4. Drugs and intracellular control mechanisms -- 5. The fate of drugs in the body -- 6. Pharmacogenetics -- 7. The nervous system -- 8. Anti-inflammatory analgesics; Gout; Antihistamines; immunosuppressive drugs -- 9. The circulatory system -- 10. The respiratory system -- 11. The diuretic drugs -- 12. The alimentary system -- 13. Chemotherapy -- Index.
Includes index.
Keywords: PHARMACOLOGY